Interações entre área foliar, volumes de calda e doses de fungicidas na persistência e no controle de doenças em soja - Chechi, Amanda (2016)
Soybean is one of the main commodities of global agribusiness, used both for consumption in natura as for the production of bran, oil and other products. Among the main factors limiting the plant production there are the diseases, especially the Asian soybean rust, caused by Phakopsora pachyrhizi. In most cases, this disease is managed with the aid of fungicides, which efficiency depends largely on the application technology. The objectives of this study were to verify if the LAI of soybean cultivars influences the choice of fungicide rate and spray volume at the application time, to analyze if the doses between 0 and 100% of the commercial fungicide rate affects the control of the disease and to quantify the reduction on the control of Asian soybean rust in response to the occurrence of simulated rainfall at different times after the fungicide application. At first, the influence of different fungicide rates and spray volumes were evaluated in soybean cultivars with different leaf area rate. At the experimental area of the Universidade de Passo Fundo, three soybean cultivars were sown: NS 5445 (LAI <6), BMX Vanguarda (LAI between 6 and 7) and BMX Ponta (LAI>7) in which there were three applications of fungicides consisting of trifloxystrobin + prothioconazole (48 days after sowing - DAS) and azoxystrobin + solatenol (67 and 88 DAS), varying doses (75%, 100% and 125% of the recommended rate) and spray volumes (100, 150 and 200 L/ha). The incidence and severity of leaf spot and asian soybean rust, LAI and grain yield were evaluated. As a result for cv. NS 5445, the spray volume of 100 L/ha and 100% of the fungicide rate were enough to control the diseases. For cv. BMX Vanguarda, a water volume of 150 L/ha and 100% of the fungicide rate were needed for effective diseases control. As for cv. BMX Ponta, the best treatment was composed by an increase of 25% in the fungicide rate with the spray volume of 200 L/ha. In the second experiment, they were tested in laboratory, the fungicide rates from 0 to 100% for two fungicides: trifloxystrobin + prothioconazole and azoxystrobin + solatenol. Soybean leaflets were collected from plants grown in greenhouse and they were dipped in appropriate fungicide solutions for five seconds. After drying on the shade, they were inoculated with a suspension of P. pachyrhizi spores (50.000 spores/mL). After 22 days incubated in a growth chamber on 23 °C and photoperiod of 12h light/dark, the leaflets were evaluated for the number of pustules/cm2. The results showed that the higher the dose of the fungicide, the smaller the number of pustules/cm2, and the treatment composed by 100% of the recommended rate was the best in the disease control. In the third experiment, the azoxystrobin + solatenol fungicide were sprayed on the plants that were grown in a greenhouse. The same spray volumes and fungicide doses of the field trial were used. After having sprayed, the plants were submitted to artificial rain of 20 mm at different times: 0.5; 1.0; 1.5; 2.0; 2.5; 3.0 h after the application and a control with and without fungicide spraying, both without the presence of artificial rain. Then leaflets were collected from the plants, identified, inoculated, incubated and evaluated as performed in the experiment 2. The closer the application time to the occurrence of rain, the lower was the control achieved by applying the fungicide. It is concluded that the rational use of fungicides to control soybean rust and leaf spot in soybean require fungicide rate and spray volume adjustments to the culture leaf area index. The reduction of fungicide rate implies in less control of the Asian soybean rust and the occurrence of rain up to three hours after fungicide application reduces the control of the disease.